2020
DOI: 10.3390/diagnostics10030163
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Profile of Deep Endometriosis Patients: Comparison of Vaginal Fluid, Endometrium and Lesion

Abstract: This work aimed to identify and compare the bacterial patterns present in endometriotic lesions, eutopic endometrium and vaginal fluid from endometriosis patients with those found in the vaginal fluid and eutopic endometrium of control patients. Vaginal fluid, eutopic endometrium and endometriotic lesions were collected. DNA was extracted and the samples were analyzed to identify microbiome by high-throughput DNA sequencing of the 16S rRNA marker gene. Amplicon sequencing from vaginal fluid, eutopic endometriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 54 publications
3
82
1
4
Order By: Relevance
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
“…Acinetobacter [20], Barnesiella [18], Comamonadaceae [20], Enterobacteriaceae [19], Flavobacterium [18], Gardnerella [17], Lactobacillus [17,18,20], Moraxellaceae [19], Prevotella [17], Pseudomonas [18,20], Sphingobium [20], Staphylococaceae [19], Streptococcaceae [17,19], Vagococcus [20] Chronic endometritis…”
Section: Healthymentioning
confidence: 99%
See 3 more Smart Citations